1981
DOI: 10.1259/0007-1285-54-643-622
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NMR exposure on living organisms. II. A genetic study of human lymphocytes

Abstract: The effects of NMR line-scan imaging procedures and static homogeneous magnetic fields of 0.5 and 1.0 tesla on cells from human blood have been investigated by examining their influence on the frequency of gross lesions, sister chromatid exchanges and on the proportion of amodal cells. Cultured human blood cells have also been submitted to extended NMR imaging exposure during active growth and division. Neither treatment had any significant effect on any of the parameters measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…On the whole our results indicate that static NMRF exposure has neither proliferative, nor activating, nor proinflammatory effects on PBMC and are consistent with earlier findings that exposure causes no adverse cytogenetic effects [Cooke and Morris, 1981;Prasad et al, 1984]. Finally the decreased proliferation of Jurkat cells after NMRF exposure is consistent with the very low concentrations of both IL-2 and [Ca 2þ ] i .…”
Section: Discussionsupporting
confidence: 92%
“…On the whole our results indicate that static NMRF exposure has neither proliferative, nor activating, nor proinflammatory effects on PBMC and are consistent with earlier findings that exposure causes no adverse cytogenetic effects [Cooke and Morris, 1981;Prasad et al, 1984]. Finally the decreased proliferation of Jurkat cells after NMRF exposure is consistent with the very low concentrations of both IL-2 and [Ca 2þ ] i .…”
Section: Discussionsupporting
confidence: 92%
“…The biological effects of high-strength magnetic fields are very complex. Although MRI is not considered hazardous to the fetus, only a few investigations have examined the teratogenic potential of this imaging modality [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. A number of mechanisms exist that could theoretically cause adverse biologic effects [5, 17, 18, 19, 20, 21, 22, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the bioeffects of magnetic resonance, particularly at high magnetic fields (2 Tesla used in this study and higher), are largely unknown. Several studies have shown that while no genetic or teratogenesis effects have been observed from high magnetic fields, reduced fetal growth and weight losses were reported in rodents exposed to magnetic fields for 16 consecutive hours [7][8][9][10]. Clearly, these observations need to be further studied prior to possible clinical protocols for prenatal MR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%